Una mirada hacia el pasado. La figura de Alejandro Magno en el teatro español del siglo XVIII. - Briante Benítez, Federico Juan (El Colegio de México, 2021)
Throughout the eighteenth century, the Bourbon monarchs devoted numerous efforts to consolidating their rather exalted concep-tion of the King and the Monarchy with the aim of putting the decrepit legacy of the last Austrias far behind them. To this end, the new Royal House of Spain focussed its attention on Greco-Roman Antiquity and on one of its supreme representatives, Alexander the Great, a regal prototype with whom the Bourbons felt fully identified. In this work we analyze the way in which this identification was exploited in the theatre, a form of artistic expression which the political powers had always used as a tool for propaganda.